2018
DOI: 10.5304/jafscd.2018.081.006
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Food Incentive Impacts on Direct-to-Consumer Sales: A Michigan Example

Abstract: Numerous interventions have been implemented at farmers markets across the United States in recent years in order to increase Supplemental Nutrition Assistance Program (SNAP) redemptions. These initiatives include ensuring that farmers markets have the technological capability of accepting SNAP and implementing financial incentive programs that provide matching benefits for the redemption of SNAP benefits. While a main objective behind these initiatives is to increase revenue to direct marketing farmers, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…These findings are also consistent with quantitative studies that show a positive economic impact for vendors participating in FM matching programs. This is important to consider in light of major funders across the country moving toward restricting match-eligible foods to fruits and vegetables only (Mann et al, 2018;Oberholtzer et al, 2012). Limiting the variety of items available for purchase may affect vendors selling items that may contribute to a market basket of healthy items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are also consistent with quantitative studies that show a positive economic impact for vendors participating in FM matching programs. This is important to consider in light of major funders across the country moving toward restricting match-eligible foods to fruits and vegetables only (Mann et al, 2018;Oberholtzer et al, 2012). Limiting the variety of items available for purchase may affect vendors selling items that may contribute to a market basket of healthy items.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found positive impacts on participating customers, including increased food security, FM use, and fruit and vegetable consumption (Pellegrino et al, 2018;Savoie Roskos, Wengreen, Gast, LeBlanc, & Durward, 2017;Young et al, 2013). While some research has explored the economic benefits to vendors, including an increase in sales and new customers (Lehnerd, Sacheck, Griffin, Goldberg, & Cash, 2018;Mann et al, 2018;Oberholtzer, Dimitri, & Schumacher, 2012), few studies to date have examined vendor perspectives on participation in matching programs. These studies conducted surveys with vendors and report that vendors participating in matching programs did not perceive program logistics as complex or burdensome to their business (Lehnerd et al, 2018;Payne et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge for local food system (LFS) advocates is managing the intersection of policy, measurement of economic impacts, and practice. There is a growing body of literature that applies different methods to measure the economics of LFSs; some examples include Conner et al, 2013;Jablonski, Schmit, and Kay, 2016;Mann et al, 2018;Miller et al, 2015. Civic leaders apnd program managers wish to know how their efforts contribute over time, but impact studies are not able to provide sufficient monitoring to gauge progress or failure toward meeting common targets for LFSs.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars point to a number of benefits, both individual and communal, derived from thriving farmers markets. For example, farmers capture more revenue in direct-selling schemes (La Trobe, 2001;Mann et al, 2018), local and regional food systems can enhance food security (Allen, 1999), markets allow consumers to signal a desire for sustainable consumption options (Seyfang, 2006), shoppers attend markets for both food purchasing and entertainment (Farmer, Chancellor, Gooding, Shubowitz, & Bryant, 2011), health benefits can accrue from increased fresh fruit and vegetable consumption (Herman, Harrison, Afifi, & Jenks, 2008), and the environment benefits from increased caloric reliance on fruits and vegetables (Godfray et al, 2010) that supplant animal-based products; these are all touted benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Community development is also seen as an indirect benefit from a successful farmers market, particularly those markets that cater to a diverse swatch of a community's population. As noted by Mann et al (2018) and others, the acceptance of Supplemental Nutrition Assistance Program (SNAP) benefits within the local food sector is perceived as a way to enhance community development via economic development benefits (Bell, Mora, Hagan, Rubin & Karpyn, 2013). A second and related example includes the spillover effects of consumer spending.…”
Section: Introductionmentioning
confidence: 99%